Pengaruh Digitalisasi Zakat Terhadap Penerimaan Dana Zakat Melalui Kepercayaan Masyarakat Sebagai Variabel Intervening: Studi Pada Wahdah Inspirasi Zakat Bone - Nur Aulia Asrani; Muhammad Yamin; Masyhuri Masyhuri (Fakultas Ekonomi Universitas 45 Surabaya, 2024)
This study aims to analyze the impact of zakat digitalization on public trust and zakat fund collection, as well as the role of public trust as an intervening variable in this relationship. Conducted at Wahdah Inspirasi Zakat (WIZ) Bone, a zakat institution that has implemented a digital system, this research employs a quantitative approach using Partial Least Square (PLS) analysis with data from 100 purposively selected muzakki, collected through questionnaires and analyzed using SmartPLS 4.0. The findings indicate that zakat digitalization positively and significantly influences public trust but does not directly affect zakat fund collection. However, public trust has a positive and significant impact on zakat fund collection and serves as an intervening variable, highlighting its key role in enhancing the effectiveness of zakat digitalization. Therefore, zakat institutions should improve transparency, accountability, and security in digital systems while increasing outreach and education to encourage more muzakki to utilize digital zakat services.